Analysis of U19 and U23 Worlds in Varese - Kleshnev, V. (BioRow, 2022)
By popular request, a race data analysis of the U19 and U23 World Rowing Championships in Varese, Italy was conducted by BioRow. Due to variable weather conditions throughout the regatta (even within a single day), it is difficult to compare the absolute rowing speeds across different categories: the average winners` speed in 12 comparable Olympic boat types (except lightweights) was even slower for the U23s in Saturday`s finals (5.02m/s, 96.2% of World Best Time) compared to the U19s on Sunday (5.07m/s, 99.2% of WBT), when four World best times were set in the JM8+, JW2x, JW4- and JW8+.